Socialization of Strengthening the Administrative System in Cermin Alam Hamlet, Tebo Regency, Jambi, Indonesia - Chotib, H. M.; Pratiwi, Widya; Hamirul, Hamirul (Indonesian Community Empowerment Journal, 2023)
The shifting of authority from the central government to regional governments and then extending it to the village level is a challenge but also an opportunity for bureaucrats to serve the community responsively. This condition requires an understanding of ideal and relevant governance in dealing with existing problems. This community service activity is a comprehensive and real effort from the entire academic community to share knowledge and knowledge related to administrative effectiveness and governance. Community service activities are carried out in the form of workshops and discussions about the administrative system in Cermin Alam Hamlet, Tebo Regency, Jambi, Indonesia. This community service activity is quite effective in increasing the knowledge aspect of village officials regarding aspects of village government administration. An increase in the knowledge score from an average of 45.56 to 87.45 shows the effectiveness of community service activities in strengthening the administrative system through workshops and discussions.